Internalization of Multicultural Education Values in Islamic Boarding Schools - Nabilla Nabilla (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
This study explores how Islamic boarding schools (pesantren) in Indonesia internalize the values of multicultural education in their daily educational practices. As institutions that traditionally emphasize Islamic teachings, pesantren have also become important spaces for nurturing tolerance, respect for diversity, and peaceful coexistence. Using a qualitative case study approach, this research identifies how these values are integrated not only through formal education but also through everyday interactions, role modeling by religious leaders (kyai and ustadz), and the communal lifestyle of the students. The findings highlight the pesantren’s unique potential in promoting inclusive attitudes and strengthening social cohesion in a culturally diverse society. The study suggests that incorporating multicultural values more explicitly into the pesantren curriculum could further enhance their role in shaping open-minded and socially responsible individuals. From the research results, it is stated that the implementation of multicultural education at Pondok Pesantren Terpadu Ushuluddin is already good. This is evident from the attitude of the pesantren leaders who always guide teachers and students in applying multicultural education.This is evidenced by teachers who do not differentiate between students based on ethnicity, race, culture, social strata, or gender in implementing multicultural education both in the classroom and in the Pondok Pesantren environment. However, there are still some teachers who have not implemented this due to a lack of ability to create educative interactions between students and teachers, as well as difficulty in creating a conducive atmosphere.